HUBUGAN ANTARA KEBERFUNGSIAN KELUARGA DENGAN KEPUASAN HIDUP (LIFE SATISFACTION) PADA ANAK - Eva Herik (Universitas Halu Oleo, 2020)
This study aims to find out the relationship between family functioning variables and life satisfaction in children. The sample of this study was students who attended SD X and SD Y and were 10 to 12 years old. The analysis used a correlation product moment from Spearman. The result of statistical analysis found significant relationship between family functioning variables and life satisfaction variables in children, with correlations r = 0.252 and p = 0.009 (p<0.05). The hypothesis test used is a normality test and a linearity test.